Two new species of the genus Uralaphorura Martynova, 1978 (Collembola: Onychiuridae) from Siberia - Babenko, Anatoly (Zootaxa, 2009)
Two new species of the genus Uralaphorura from Yakutia, Russia, U. varicellata sp. nov. and U. yanensis sp. nov. are described and illustrated. The former is characterised by an increased and unstable number of pseudocelli, the latter is similar to U. schilovi (Martynova, 1976) but differs in having pointed tibiotarsal setae and the absence of unpaired axial setae on the tergum of Abd.VI. Some remarks on U. schilovi based on a study of the type-material are also given.